Effect of Late Season Management Practices on Soybean Seed Filling and Yield - F. E. Baronio; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2020)
For soybean (Glycine max[L.] Merr.), final seed yield is primarily explained by modifications in the seed number per unit area. However, changes in individual seed weight can contribute to variations in seed yield. Final seed weight is defined by the amount of biomass accumulated in seeds per day (i.e., rate of seed growth) and the duration of this phase (i.e., number of days for seed filling). During the seed filling period, the seed growth rate and the duration are sensitive to growing conditions. Thus, any limitation on resources availability (e.g., water, radiation, and nutrients) during this period can be translated into reductions in seed weight that ultimately will affect final seed yield. The objective of this study was to identify late-season management practices potentially contributing to increased final seed weight and seed yield in soybeans.
Keywords: Management practices; soybeans; seed filling; yield